Effectiveness of Non-ASN Recruitment in Human Resources Placement in Village Government - Fadjar Tri Sakti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The recruitment of Non-Civil Servant Employees (Non-ASN) has become a crucial issue in local government human resource management due to the limited number of civil servants that affects public service effectiveness. This study aims to analyze the effectiveness of the Non-ASN recruitment system in human resource placement at Pungkur Village, focusing on the lock-regional practice prioritizing local residents. Theoretically, this study refers to recruitment theory, job placement theory, and organizational effectiveness theory. A qualitative case study method was employed, using interviews, observations, and document analysis, with data analyzed through Miles & Huberman’s interactive model. Findings reveal that local-based Non-ASN recruitment effectively reduces unemployment, strengthens social cohesion, and supports public service delivery. Employee placement is carried out flexibly, both in skilled positions and general tasks, facilitating local HR management. This study highlights Non-ASN recruitment as an adaptive strategy for local bureaucracies.